The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1016/j.neuron.2006.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Transient and Selective Overexpression of Dopamine D2 Receptors in the Striatum Causes Persistent Abnormalities in Prefrontal Cortex Functioning

Abstract: Increased activity of D2 receptors (D2Rs) in the striatum has been linked to the pathophysiology of schizophrenia. To determine directly the behavioral and physiological consequences of increased D2R function in the striatum, we generated mice with reversibly increased levels of D2Rs restricted to the striatum. D2 transgenic mice exhibit selective cognitive impairments in working memory tasks and behavioral flexibility without more general cognitive deficits. The deficit in the working memory task persists eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
480
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 477 publications
(519 citation statements)
references
References 63 publications
32
480
4
Order By: Relevance
“…Studies have also suggested an increased affinity of D 2 receptors for DA in schizophrenia, which may produce D 2 receptor supersensitivity in the NAc, contributing to psychosis [79]. In an interesting animal model correlate to these studies, transient overexpression of D 2 receptors in the striatum of mice resulted in deficits in prefrontal working memory, resembling some of the features of human schizophrenia [80]. Studies such as these indicate that alterations in DA receptor expression (or function) can result in a dysfunctional reward system.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also suggested an increased affinity of D 2 receptors for DA in schizophrenia, which may produce D 2 receptor supersensitivity in the NAc, contributing to psychosis [79]. In an interesting animal model correlate to these studies, transient overexpression of D 2 receptors in the striatum of mice resulted in deficits in prefrontal working memory, resembling some of the features of human schizophrenia [80]. Studies such as these indicate that alterations in DA receptor expression (or function) can result in a dysfunctional reward system.…”
Section: Reviewmentioning
confidence: 99%
“…Kellendonk et al . [80] attempted to model this D 2 receptor elevation in genetically engineered mice, in which they transiently and selectively overexpressed D 2 receptors in the striatum including in the caudate putamen, the NAc, and olfactory tubercle. It was found that 30% of striatal MSNs overexpressed these engineered receptors, thereby elevating the D 2 receptor level to about 15% higher than that of normal mice.…”
Section: Reviewmentioning
confidence: 99%
“…The PFC receives key ascending dopaminergic inputs from the midbrain and other subcortical areas (Kellendonk et al., 2006; Tekin & Cummings, 2002), and emerging evidence suggests the existence of an optimal level of dopamine needed for efficient PFC functioning (Goldman‐Rakic, Muly, & Williams, 2000). Two genes that have been associated with various psychiatric and neurological disorders and which have attracted attention due to their role in cognitive and emotional processes are the genes encoding for the enzyme catechol‐O‐methyltransferase ( COMT ; Dickinson & Elvevåg, 2009; Scheggia, Sannino, Luisa Scattoni, & Papaleo, 2012; Tunbridge, Harrison, & Weinberger, 2006) and the dopamine receptor D2 ( DRD2 ; Frank & Fossella, 2011; Huertas, Bühler, Echeverry‐Alzate, Giménez, & López‐Moreno, 2012; Kellendonk et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Two genes that have been associated with various psychiatric and neurological disorders and which have attracted attention due to their role in cognitive and emotional processes are the genes encoding for the enzyme catechol‐O‐methyltransferase ( COMT ; Dickinson & Elvevåg, 2009; Scheggia, Sannino, Luisa Scattoni, & Papaleo, 2012; Tunbridge, Harrison, & Weinberger, 2006) and the dopamine receptor D2 ( DRD2 ; Frank & Fossella, 2011; Huertas, Bühler, Echeverry‐Alzate, Giménez, & López‐Moreno, 2012; Kellendonk et al., 2006). COMT is responsible for breaking down ~50–60% of dopamine produced in the frontal cortex (Yavich, Forsberg, Karayiorgou, Gogos, & Männistö, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation